Nicotine patch preloading for smoking cessation (the preloading trial): study protocol for a randomized controlled trial - Lindson-Hawley, Nicola; Coleman, Tim; Docherty, Graeme; Hajek, Peter; Lewis, Sarah; Lycett, Deborah; McEwen, Andy; McRobbie, Hayden; Munafo, Marcus R.; Parrott, Steve; Aveyard, Paul (BioMed central, 2014)
Background: The use of nicotine replacement therapy before quitting smoking is called nicotine preloading. Standard smoking cessation protocols suggest commencing nicotine replacement therapy only on the first day of quitting smoking (quit day) aiming to reduce withdrawal symptoms and craving. However, other, more successful smoking cessation pharmacotherapies are used prior to the quit day as well as after. Nicotine preloading could improve quit rates by reducing satisfaction from smoking prior to quitting and breaking the association between smoking and reward. A systematic literature review suggests that evidence for the effectiveness of preloading is inconclusive and further trials are needed.